Managing Mask Waste in the New Normal Era - Prasida, Dita Wasthu (Interdisciplinary Social Studies, 2023)
Background: The COVID-19 pandemic has changed the dynamics of global landfills so it needs special attention. Personal protective equipment, used masks, gloves are the main contribution to the volume of waste. The handling of infectious waste is a major global concern for public health and environmental sustainability if not handled properly. This can cause the spread of deadly diseases because waste acts as a vector for corona virus deasease that lasts up to 7 days in COVID-19 waste such as masks. Aim: To identify mask waste management in the new normal era. Method: The research method used in this study is a literature review by analyzing journals about mask waste management in the new normal era from Google Scholar between 2019-2021. Findings: Mask waste management in the new normal era can be implemented well by the community. Further socialization and monitoring from local governments is needed so that people understand household medical waste management properly.